THE ASSOCIATION OF HISTORY OF PREVIOUS SPONTANEOUS ABORTION OR STILLBIRTH WITH SUBSEQUENT RISK OF GESTATIONAL DIABETES MELLITUS - Kocevska, Ana; Skeparovska, Kristina; Mucha, Argjent (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Introduction: Gestational diabetes mellitus (GDM) is a disorder of glucose metabolism, with varying degrees of clinical severity, that first appears during pregnancy. The aim of this study is to examine the association of a history of previous spontaneous abortions and stillbirths with the occurrence of GDM in the current pregnancy. Material and methods: The study included all pregnant women who underwent an OGTT (Oral Glucose Tolerance Test) for the diagnosis of GDM, in the period of 3 years, at the University Clinic for Endocrinology, Diabetes and Metabolic Disorders – Skopje. Patients were divided into two groups: Study group (with a positive OGTT) and Control group (with negative OGTT). Anamnestic and laboratory parameters were provided by medical documentation. Results: The analysis indicated that pregnant women with positive OGTT had a significantly higher number of previous miscarriages compared to pregnant women with a negative OGTT (Pearson Chi-square=8.6521, df=3, p=0.0343).  According to the analysis, pregnant women with a positive OGTT had significantly more stillbirths compared to pregnant women with a negative OGTT status (Pearson Chi-square=9.5779, df=2, p=0.0083). Conclusion: History of previous miscarriages significantly increases the risk of gestational diabetes mellitus. A history of one miscarriage significantly increases the likelihood of gestational diabetes mellitus by 1.599 times. A history of two miscarriages significantly increases the likelihood of gestational diabetes mellitus by 2.339 times. Pregnant women with a positive history of one previous stillbirth are 4.365 times more likely to have a positive OGTT status compared to pregnant women who have not had any stillbirths. Keywords: gestational diabetes mellitus, spontaneous abortion, stillbirth.